Large variations in indirect N2O emission factors (EF5) from coastal aquaculture systems in China from plot to regional scales. (15th July 2021) - Yang, Ping; Huang, Jiafang; Tan, Lishan; Tong, Chuan; Jin, Baoshi; Hu, Beibei; Gao, Changjun; Yuan, Junji; Lai, Derrick Y.F.; Yang, Hong
Highlights: EF5 from aquaculture ponds exhibited large spatiotemporal variations. DOC:NO3 − -N mass ratio governed the temporal variations in EF5 . Feed conversion rate and salinity affected the spatial variations in EF5 . EF5 from aquaculture ponds was substantially higher than the IPCC default value. Abstract: Aquaculture ponds are important anthropogenic sources of nitrous oxide (N2 O). Direct N2 O emissions arising from feed application to ponds have been widely investigated, but indirect emissions from N2 O production from residual feeds in pond water are much less understood and characterized to refine the IPCC emission factor. In this study, we determined the concentrations and spatiotemporal variations of dissolved N2 O and NO3 – –N in situ in three aquaculture ponds at the Min River Estuary in southeastern China during the culture period over two years, and calculated the indirect N2 O emission factor (EF5 ) for aquaculture ponds using the N2 O–N/NO3 – –N mass ratio methodology. Our results indicated that the EF5 values in the ponds over the culture period ranged between 0.0007 and 0.0543, with a clear seasonal pattern which closely followed that of the DOC:NO3 — N ratio. We also observed significant spatial variations in EF5 among the three ponds, which could be attributed to the difference in feed conversion rate. In addition, we assessed the EF5 values from aquaculture ponds in five regions of the Chinese coastline across the latitudinal gradient from the tropical to the temperate zones. The average EF5 value from aquaculture ponds across the five coastal regions was 0.0093±0.0024, which was approximately 3.7 times of the IPCC default value for rivers and estuaries (0.0025). Moreover, the EF5 values demonstrated considerable spatial variations across these coastal regions with a coefficient of variation of 59%, which were largely related to the difference in water salinity. Our findings filled a key knowledge gap about the indirect N2 O emission factor from aquaculture ponds, and provided field evidence for the refinement of EF5 value currently adopted by IPCC in the national greenhouse gas inventory.